2009
DOI: 10.1124/dmd.108.026328
|View full text |Cite
|
Sign up to set email alerts
|

Use of Human Microsomes and Deuterated Substrates: An Alternative Approach for the Identification of Novel Metabolites of Ketamine by Mass Spectrometry

Abstract: ABSTRACT:In vitro biosynthesis using pooled human liver microsomes was applied to help identify in vivo metabolites of ketamine by liquid chromatography (LC)-tandem mass spectrometry. Microsomal synthesis produced dehydronorketamine, seven structural isomers of hydroxynorketamine, and at least five structural isomers of hydroxyketamine. To aid identification, stable isotopes of the metabolites were also produced from tetra-deuterated isotopes of ketamine or norketamine as substrates. Five metabolites (three hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 28 publications
4
74
0
4
Order By: Relevance
“…Furthermore,f ragment ions formed from the [M + H] + ion of Ket (Figure 1c) matched those previously reported, [11] and fragments obtained from Ket standard (Figure S2 a). Not only Ket, but also its main metabolites could all be detected with our setup.…”
supporting
confidence: 83%
“…Furthermore,f ragment ions formed from the [M + H] + ion of Ket (Figure 1c) matched those previously reported, [11] and fragments obtained from Ket standard (Figure S2 a). Not only Ket, but also its main metabolites could all be detected with our setup.…”
supporting
confidence: 83%
“…In the first approach, a labeled aglycon served as a substrate, as in a recent study where pooled human liver microsomes were used for a similar biotransformation (Turfus et al, 2009). In this case, 4-fold deuterated T was successfully glucuronidated by strain DB53 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has also been used as a new psychoactive substance since the 1960s [25,26] and several intoxication cases have been reported [25,27]. Some research groups have studied the in vitro metabolism of KET [28,27] and identified two major metabolites: norketamine (NK) and dehydronorketamine (DHNK). Additionally, these studies [28,27] found several isomers of hydroxyketamine (HK) and hydroxynorketamine (HNK).…”
Section: Ketamine and Metabolitesmentioning
confidence: 99%
“…Some research groups have studied the in vitro metabolism of KET [28,27] and identified two major metabolites: norketamine (NK) and dehydronorketamine (DHNK). Additionally, these studies [28,27] found several isomers of hydroxyketamine (HK) and hydroxynorketamine (HNK). However, the confirmation of these metabolites was not done by AMMS.…”
Section: Ketamine and Metabolitesmentioning
confidence: 99%
See 1 more Smart Citation